Main Organizational Factors that Influence Student Satisfaction in Universities - Palacio-Fierro, Andrés (2017)
Education is not a 5-star hotel service because a student is not always able to get what he or she wants (usually good grades) because it is not enough just to go to class or pay a tuition, additionally, these people must give time, dedication and effort, aspects by which it differs from the rest of goods and services that are offered.  For this reason, among others, there are opposing opinions about how students should be treated in a university, however, they are still users of a service, therefore, their requirements must be met. Consequently, the student can be treated as customer, consumer or co-producer, no matter what it is called, as long as, someone cares for them. Consequently, the general objective of this study is to perform an analysis of the main factors that influence student satisfaction, with the purpose of contributing to the knowledge that universities should have about them.  For which, the scope of the research focuses only on the factors most controllable by a university, through a documentary review that analyzed a large amount of contributions made on student satisfaction by researchers at a global level, in order to achieve an inclusive study with an international view.